The Role of Perceived Business Value in Mediating the Use of Social Media on the Marketing Performance of MSMEs in Banyumas, Indonesia: Partial Least Square Approach - Sulasih Sulasih; Sarpini Sarpini; Sidik Rohiwan (Budapest International Research and Critics University, 2023)
The use of media is goal-oriented and motivational according to the needs of MSMEs in choosing media, including marketing products, establishing communication with consumers, and accessing information. This type of research is quantitative while the sampling technique uses Lemeshow with a purposive sampling method. The results of this study indicate that the use of social media affects performance and also the perception of business value from the use of social media. Meanwhile, perceived business value also has a positive and significant impact on business performance. Furthermore, perceived business value is also able to significantly mediate the influence of social media use on business performance. These results confirm that good use of social media can increase and strengthen the business value felt by MSME actors in Banyumas, which will also have an impact on improving business performance. The originality of this research uses perceived business value variables which are rarely studied in the MSME context. In general, perceived business value is usually implemented in companies, while MSME businesses also need to understand that with good use of social media, the perceived business value will also increase and will have an impact on marketing performance. This study is expected to make a significant contribution to MSME owners in understanding the extent to which social media use plays a role in MSME performance through Perceived Business Value. The greater the benefits felt by MSMEs related to the use of social media, the higher their performance.